Determinants for the selection of young middle-distance running talents in Athletics - Benalia, El Hadi; Mahour Bacha, Mourad (Journal of Human Sciences, 2023)
The aim of this study was to determine reality of the selection young middle-distance talents in athletics and for that, we conducted a descriptive survey research a group coaches (40) trainers chosen randomly and after two processes of discharge and statistical treatment using the test of good conformity, we concluded that the problem with tests that are not standardized between Athletic Trainers, due to the absence in Algeria of a methodology for systematically organizing selection and defining the characteristics of youth sports talent based on the evaluation of the biological, physical and morphofunctional capabilities in order to optimally identify the future champion and identify on the most indicative criteria for predicting athletic success, the researcher recommended the need for coaches to pay attention to morphofunctional measurements and consider them as basic determinants when using the selection talent process steps.